A Breif Overview on Alzheimer’s Disease: Potential Targets - Kondumahanti V. N. Lakshmi; S. K. Abdul Rahaman; G. Sai Sri Lakshmi (Current Innovations in Disease and Health Research Vol. 2, 2023)
The aim of this article is to explore the potential targets of Alzheimer’s Disease (AD) as it is triggered through many pathways. The most common cause of dementia is Alzheimers disease. Averagly, 6.2 millions Americans aged 65 and older are living with Alzheimers type of dementia today. This number could increase to 13.8 million by 2060. FDA has approved few drugs like Donepezil, Galantamine, Rivastigmine and Memantine for AD. These drugs mainly act on two targets like Acetylcholinesterase enzyme (Drugs like like Donepezil, Galantamine, Rivastigmine and NMDA receptors (Drug like Memantine). But many potential targets are involved in AD. Acetylcholinesterase and tau proteins are widely investigated in the brain tissues in this disease, but many factors may trigger the pathogenesis of this disease. The anomalous processing of APP by \(β\)-secretases and \(γ\)-secretases leads to production of A\(β\)40 and A\(β\)42 monomers, which further oligomerize and aggregate into senile plaques that leads to impairement in neuronal transmission. Generally targets like acetylcholinesterase, Amyloid plaques and Tau proteins are known to cause Alzheimers Disease. But there are various mechanisms like Neurotransmitters involvement (GABA, Histaminergic and NMDA), Caspases, beta arrestins, Involvement of ACE, NO are also involved in the pathogenesis of Alzheimers disease. Some of the gene mutations like APOE, Presenilin (PSEN 1), Presenilin 2 (PSEN 2) also paves the way for Alzheimers disease. The present study was planned to explore the various unexplored targets of Alzheimers disease.